ANALISIS FAKTOR PEMILIHAN KB SUNTIK 3 BULAN PADA AKSEPTOR KB SUNTIK - Meiliza; Titin Dewi Sartika Silaban; Tuti Farida (Poltekkes Kemenkes Medan, 2022)
Contraception is a tool used to avoid or prevent pregnancy as a result of the meeting between the mature egg cell and the sperm cell. The injectable contraceptive for 3 months is Depo Medroxyprogesterone Acetate (Depo-Provera), containing 150 mg of DMPA. Given every 3 months by injection intramuscularly (IM) in the buttocks area. This type of research is an analytic survey with a cross-sectional approach, this research was conducted at the regional health center of Ogan Ilir Regency in January-July 2021. The sample was selected by non-random sampling so that a sample of 88 respondents was obtained who became injectable family planning acceptors. Variables were measured using a questionnaire. The results of the chi-square test, there is a significant relationship between knowledge and the choice of 3-month injection KB p.value 0.049 < = 0.05, there is a significant relationship between husband's support and the choice of 3-month injection KB p.value = 0.001 < = 0.05, there is a relationship between the role of health workers and the choice of 3-month injection KB p.value = 0.002 < 0.05, there is a relationship between income and the choice of 3-month injection KB .value = 0.029 < 0.05, and there is no significant relationship between information media and the choice of 3-month injection KB p.value = 1,000 > = 0.05. This study concludes that there is a relationship between knowledge, husband's support, the role of health workers, and income with the choice of 3-month injection KB, and there is no relationship between information media and the choice of 3-month injection KB.